2017
DOI: 10.3389/fpsyg.2017.00643
|View full text |Cite
|
Sign up to set email alerts
|

Upper Limb Asymmetry in the Sense of Effort Is Dependent on Force Level

Abstract: Previous studies have shown that asymmetries in upper limb sensorimotor function are dependent on the source of sensory and motor information, hand preference and differences in hand strength. Further, the utilization of sensory and motor information and the mode of control of force may differ between the right hand/left hemisphere and left hand/right hemisphere systems. To more clearly understand the unique contribution of hand strength and intrinsic differences to the control of grasp force, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 25 publications
(45 reference statements)
2
9
0
Order By: Relevance
“…The total amount of the requested force had a relevant effect on the performance, increasing the difference between the two hands and its variability. Further, the bias error highlighted that the left hand applied more force than the right for the lower target force, but this effect was decreased and even inverted for the higher target force, consistently with previous results in sequential [8,9] and concurrent [10] matching task. The results of the present study extend the previous findings, highlighting that this effect was not influenced by the handedness.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The total amount of the requested force had a relevant effect on the performance, increasing the difference between the two hands and its variability. Further, the bias error highlighted that the left hand applied more force than the right for the lower target force, but this effect was decreased and even inverted for the higher target force, consistently with previous results in sequential [8,9] and concurrent [10] matching task. The results of the present study extend the previous findings, highlighting that this effect was not influenced by the handedness.…”
Section: Discussionsupporting
confidence: 89%
“…the performance seemed to be influenced by the specialization of the brain hemisphere, evolving independently from handedness. The significant effect of the left hand position in right-handed individuals [11] was supported by the dichotomous model [3] observed in motor [7] and force tasks [8,9]. This model suggests that during bimanual activities, the dominant right arm relies more on visual feedback, while the non-dominant left arm on proprioceptive feedback.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In this context, pioneer neuroanatomical studies showed that the dominant hemisphere may have higher corticospinal tract density [ 77 , 78 ], although the neurophysiology underlying brain asymmetries is still controversial, with some authors suggesting that the dominant hemisphere exhibits larger cortical representation areas with lower excitability [ 79 ], while others report the opposite [ 80 , 81 ], or even no difference [ 82 , 83 , 84 ]. It has been recently demonstrated that a laterality asymmetry possibly leads to a more pronounced MEP distribution on the dominant hemisphere compared to the non-dominant side in healthy right-handers [ 85 ], and that patients with motor and movement disorders exhibit disruptions of motor unit recruitment and discharge patterns [ 86 , 87 , 88 , 89 ], which may affect dominant and non-dominant sides differently [ 90 ]. However, the lack of similar data in PSP precludes a better understanding of laterality asymmetries in these patients and stimulates further studies on this intriguing topic.…”
Section: Discussionmentioning
confidence: 99%
“…Modulation of motor output has been reported to depend on central and peripheral processes in relation to sense of force or tension and sense of effort [5]. Sense of force originates from articular, muscular, and cutaneous receptors, whereas sense of effort arises from the perception of descending motor commands [6][7][8]. However, the contribution of these two mechanisms on performance modulation ability remains controversial, especially in patients with musculoskeletal impairments (e.g., end-stage knee osteoarthritis) or after surgery (e.g., total knee arthroplasty), for whom muscle and/or joint damages generate a discrepancy between sense of force and sense of effort [5,9,10].…”
Section: Introductionmentioning
confidence: 99%